Asthma phenotypes in children - Bush, Andrew (Henry Stewart Talks, 2011)
Severe asthma, Getting the basics right, Rarity of genuine severe therapy resistant asthma, Differences between childhood and adult asthma, Protocol driven investigations to determine nature of any inflammation, Phenotype discordance, Steroid responsiveness, Presence of fixed airflow obstruction, Exacerbating phenotype particularly difficult to treat
Updated at 2015/09/30, Archived at 2018/01/31